Identification of talent in a multinational corporation and the challenges, problems and biases surrounding it - Sampson, Daniel (My University, 2013)
There has been a growing interest in talent management since the article by McKinsey in 1998, declaring the ‘war for talent’. This so-called ‘war for talent’ has been sparked by, differentiation of employees, the need for global leaders and so forth. Multinational corporations which implement a differentiated workforce are required to identify who their talented employees are, because they will not provide all employees with the same development and career paths. Furthermore, organisations are required to identify who is talented, because merely containing talent per se is of little strategic value, if it is not identified and put to task. The aim of the study is to investigate the challenges that MNCs face in identifying internal talent, the biases involved in the identification process, how intransitivity is taken into account when identifying talent and does talent identification ever go wrong. To achieve this aim, this paper has utilised an empirical research approach, based on utilising a qualitative, semi-structured interview methodology and a case study. This study has found that talent identification does go wrong in the case company and one of the main reasons for the failure is the lack of consensus on who is talent in the organisation. In addition, this study found that homophily is one of the biases in the identification process. The main weakness of this study is the paucity of line or business managers, classed as ‘evaluators of talent’, participating in the study. There is only one participant who is classed as an evaluator of talent. This is a weakness, because there is a lack of comparison material for the responses from the single evaluator of talent. This paper contributes at the general level to the empirical and qualitative research on global talent management and specifically, to the challenges that MNCs face in internal talent identification and why it can go wrong.
Keywords: Global Talent Management (GTM); Internal Talent Identification; Global Talent; High Potentials; Multinational Corporation (MNC); fi=Master's Degree Programme in International Business|